Telomere length distribution on individual chromosome arms in patients with bronchial asthma - M. Sh. Barkovskaya; E. A. Blinova; J. V. Konyahina; M. I. Leonova; V. M. Nepomniashchikch; D. V. Demina; V. S. Kozhevnikov; V. A. Kozlov (Бюллетень сибирской медицины)
Objective. The purpose of this study was to evaluate the length of telomeres in the arms of individual chromosomes in patients with bronchial asthma (BA).Materials and methods. The study included patients with BA (n = 10, the mean age (44 ± 8.2) years) and healthy donors (n = 10, the mean age (44 ± 8.4) years). Metaphase spreads obtained from peripheral blood mononuclear cells were used. At the time of sampling BA patients received treatment at the Clinic of Immunopathology, Novosibirsk. BA was diagnosed by physicians according to GINA-2016. For measurement of telomere length on individual chromosome arms we used quantitative fluorescent in situ hybridization with a PNA-probe specific for telomeres. We used inverted DAPI banding for chromosome identification (according to ISCN-2013). For each individual 5 metaphase cells were analyzed. We applied the newly developed MeTeLen software to estimate the telomere repeats quantity (http:// www.bionet.nsc.ru/en/development/application-development/development-of-a-computer/metelen.html) in metaphase images. For enhanced image analysis compared with the previously developed programs, we included estimation of background signal and correction of defects of the optical system.Results. Comparing of telomere length show, that telomeres in the certain chromosome arms (4q, 5q, 9p, 10 q, 11p, 13p, 15q, 18q, 19q) in BA are significantly shorter than in corresponding group of donors (p < 0.05, Mann – Whitney U-test). For both studied groups we also evaluated telomere sequences shortened and elongated relative to the average telomere length in the group (p < 0.05, Wilcoxon-signed-runk test). The following differences and similarities between the telomere profiles of patients and donors were determined: the telomere sequences 4p, 6q, 8p were elongated and 2q, 9q, 11p, 15q were shortened relative to the average telomere length in BA patients. Moreover, this telomere sequences did not differ from the average telomere length in the group of donors. At the same time, the telomere sequences 12p, 16p, 17p, 19p were significantly shorter, and 3p was longer than the average telomere length in both groups.Conclusions. We guess, that the observed significant shortening of telomere length on individual chromosome arms in BA, as compared to donors, is relevant in pathogenesis of this disorder. The revealed features of telomere profile of patients with BA may be a result of different telomere length maintenance mechanisms and may influence to the development of asthma that needs further study.